THE ANALYSIS OF THE SERVICE QUALITY ON FRONT OFFICE DEPARTMENT IN BALI NUSA DUA HOTEL - Sanjaya, Wayan Kiki; Wijaya, A.A. Agung; Aryati, Kadek Feni; Rafael, Reinaldo (Institut Pariwisata dan Bisnis Internasional, 2020)
This study analyzes the guest satisfaction level of service quality on front office department in Bali Nusa Dua Hotel. As many hotels are emerging up, hence companies being required to improve the service quality on front office department in order to achieve customer satisfaction. In reality, although in generally, the services in Bali Nusa Dua Hotel is good, but having some shortcomings, this became an obstacle in improving the service quality. Therefore, the problem raised in this study is how the service quality and alternative strategies in improving the service quality on front office in Bali Nusa Dua Hotel. This is a quantitative descriptive research. The data of research were obtained from observations, questionnaires, interviews, and documentation studies. The data were further tabulated with the results of the study which found that although the average guest were satisfied with the front office service, empathy is needed to be optimized as one of the alternative strategies and as a screening study that led to the satisfaction of the guests staying overnight.